Vallankumous valkoisen rodun pelastuksena: James Masonin Siege turvallistamisen ja kehysanalyysin silmin - Tiitinen, Miikkael (2025)
The thesis examined James Mason’s Siege through the frameworks of securitization theory and frame analysis. The aim was to determine how threats directed at the white race were framed in the text, what strategies and tactics were proposed in response to these threats, and how violent action was justified. The theoretical-methodological framework combined the Copenhagen School’s securitization theory with a frame analysis approach suitable for examining social and political movements. The research questions focused on the diagnostic frame—what was defined as a threat—, the prognostic frame—what solutions were offered—, and the motivational frame—how action was legitimized—, as well as how these frames appeared within the context of securitization. Based on the analysis, Siege was found to depict the white race as being under existential threat from a societal “System” portrayed as driven by Jews and liberal multiculturalism. Furthermore, the internal fragmentation of the far right was interpreted as a unique, internally generated threat. The proposed solution involved revolutionary action, rejection of conventional political participation, detachment from the “System,” and adoption of leaderless resistance. Justification for such violent actions was constructed through the perceived necessity of preserving the white race, historical references, the reinforcement of enemy images, and a moral duty to defend the in-group. Siege was understood as a multidimensional work, which partly explained its ongoing relevance. It was seen to function simultaneously as a strategic manual, an apocalyptic prophecy, and a narrative of far-right identity. Despite its centrality, Siege had remained underexamined in academic research. Its thorough analysis contributed to the understanding of radicalizing far-right ideologies. The integration of securitization theory and frame analysis offered a novel approach to studying extremist movements and provided insights that could be applied in the prevention of radicalization.